Insights for Opponents on fostering interaction in the public defence of a doctoral dissertation - Laajalahti, Anne; Virtanen, Ira A. (Prologos ry, 2024)
The public defence of a doctoral dissertation is a multifaceted, demanding interaction situation, in which the Doctoral Candidate and the Opponent have a conversation about the Candidate’s doctoral disser-tation. The public defence is an honoured tradition and, in many countries, one of the key celebratory moments in academia. In Finland, the event is public and rather formal. The public defence has received little focus in research and academic discussion from the perspective of social interaction, in which the Opponent has a central role. The interpersonal communication competence of the Opponent largely determines the nature of the public defence. Hence, there is need for guidelines and support for the Op-ponents’ communication. The aim of our article is to describe the typical conventions of Finnish public defence for those unfamiliar with them and provide insights into public defence as an interaction situa-tion. Additionally, we offer communication guidelines for the Opponents on how to construct effective and appropriate interaction in public defence, and help those granted the honour to prepare and conduct their duties competently. We cover both the interpersonal conversation between the Candidate and the Opponent, and the engagement with the listeners.
Keywords: doctoral defence; doctoral viva; Opponent; public defence; vastaväittäjä; viestintä; vuorovaikutus; väitös; väitöstilaisuus; communication; social interaction; fi=Viestintätieteet|en=Communication Studies|